Photon-In/Photon-Out Soft X-ray Spectroscopy at the TPS 45A Beamline. Issue 2 (4th March 2017) - Dong, C.-L.; Chiou, J.-W.; Tsai, H.-M.; Fu, H.-W.; Lin, H.-J.; Chen, C.T.; Pong, W.-F.
Abstract : Owing to the current energy crisis and extreme changes in the global climate, there is great interest in finding renewable energy resources. Vast progress has been made in the development of new materials related to renewable energy, and their physical/chemical properties can be tailored by nanostructuring and other advanced synthetic approaches. In many important energy systems, such as solar hydrogen systems, the atomic/electronic structures of materials and fundamental interfacial phenomena of systems critically determine the energy conversion efficiency of materials [1, 2 ]. Without knowledge of the fundamental electronic structures of the materials during conversion reactions, better engineering of the material for practical use is difficult. Understanding and controlling the interfaces in energy generation/conversion/storage materials requires in-situ/operando approaches [3, 4 ]. The Taiwan Photon Source (TPS) Soft X-ray Spectroscopic beamline provides the capabilities for X-ray absorption (XAS) and X-ray emission (XES) spectroscopies, which can be utilized to investigate unoccupied (conduction-band) and occupied (valence-band) electronic states, respectively. Moreover, resonant inelastic X-ray scattering (RIXS) can be used to study intra-band (including d - d or f - f excitations) and inter-band (charge transfer) transitions [5, 6 ]. The former provides details about electronic energy splitting in various crystal fields and the latter involves electron transfer between a metal and a ligand, which determines chemical activity [7, 8 ].